2020
DOI: 10.1177/2278533720964928
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Shared Leadership in Managing Conflicts in Multigenerational Teams: A Research Framework

Abstract: With multigenerational teams becoming ubiquitous in contemporary organisations, this article aims to address the need to understand the dynamics within such teams. The study proposes a conceptual framework to examine the role of shared leadership in multigenerational teams in promoting positive team outcomes for such teams. Potential differences in work values, attitudes and behaviours among different generations are likely to predispose multigenerational teams to a higher probability of conflicts, which may n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 102 publications
(258 reference statements)
0
2
0
1
Order By: Relevance
“…As such, they might contribute beyond their capacity. Researchers argue that leadership is an information resource that could aid organisations in building, solving conflict and protecting their means and objectives (Bhayana et al, 2021). Prior studies revealed that a leader is a stable information resource that prioritises the project by developing a professional team (Crosby and Bryson, 2010).…”
Section: Servant Leadership and Project Management Effectivenessmentioning
confidence: 99%
“…As such, they might contribute beyond their capacity. Researchers argue that leadership is an information resource that could aid organisations in building, solving conflict and protecting their means and objectives (Bhayana et al, 2021). Prior studies revealed that a leader is a stable information resource that prioritises the project by developing a professional team (Crosby and Bryson, 2010).…”
Section: Servant Leadership and Project Management Effectivenessmentioning
confidence: 99%
“…Therefore, B.A. Kaifi et al (2012); C. Bhayana et al (2021) point out that managers need to learn more about their employees' job satisfaction, their expectations, and their outlook, precisely at a time when new generations are merging with previous ones. One of the ways to overcome such conflicts among Conflict of Ukrainian Generations X and Y... personnel is precisely to investigate and analyse the dominant values of these generations.…”
Section: Introductionmentioning
confidence: 99%
“…Este liderazgo compartido facilita la movilización de los conocimientos e innovaciones (Brown, MacGregor y Flood, 2020), la satisfacción laboral y el compromiso organizativo (Liu y Werblow, 2019), el aprendizaje, la evaluación critica de ideas y la cultura abierta (Lyndon y Pandey, 2019). Varios estudios han analizado la relación entre el liderazgo compartido y el desempeño organizacional o del equipo, y han evidenciado una relación positiva (Bhayana, Gupta y Sharda, 2021;Cook, Zill y Meyer, 2020;D'Innocenzo, Mathieu y Kukenberger, 2016;Hsu, Li y Sun, 2017;Müller, Pintor y Wegge, 2018;Salas-Vallina, Ferrer-Franco y Herrera, 2020).…”
Section: Introductionunclassified